Source identification problems for the neutron transport equations - Taskin, A. (KARAGANDA STATE UNIV, 2024)
In this study, the time-dependent source identification problem for the two-dimensional neutron transport equation was studied. For the approximate solution of this problem a first order of accuracy difference scheme was presented. Stability estimates for the solution of these differential and difference problems were established. Numerical results were given.
Keywords: identification problem; neutron transport equation; difference scheme; differential equation; stability inequality; RIGHT-HAND SIDE; INVERSE PROBLEM; NUMERICAL-SOLUTION; PARAMETER; Mathematics